A new literal translation from the original Greek, of all the apostolical epistles : with a commentary, and notes, philological, critical, explanatory, and practical, in three volumes / by James Macknight D.D., author of A harmony of the Gospels, &c. - Bible. (Tufts University. Tisch Library., 2016)
Volume 1 of 3.; The second edition.; 1 online resource (3 volumes); With a list of subscribers in vol. 1, and a preliminary leaf of errata and advertisements in vols. 2-3.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English short title catalogueT144007